Bandung City's Cikapundung River Water Quality Status Using Pollution Index for Fisheries Development - Alfiansyah, Robby; Hasan, Zahidah; Haetami, Kiki; Sahidin, Asep; Herawati, Heti (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The Cikapundung River currently supports fisheries activities through carp cultivation, utilizing the river flow. Currently, domestic waste discharge, driven by the increasing growth of settlements around the river, has the potential to affect the water quality in the Cikapundung River. Information is needed regarding the quality status of the Cikapundung River so that management can be carried out according to its designation. This study was conducted in January 2024 using the pollution index (IP) method to measure its water quality. The research location was divided into five stations based on anthropogenic activities at each location. The water quality status of the Cikapundung River is classified as lightly polluted according to class II and class III quality standards. The Biochemical Oxygen Demand (BOD) and Total Suspended Solid (TSS) parameters are the causes of the high IP value in this study. The highest TSS and BOD values ​​are at station 4, which is a densely populated area with fisheries activities. The Cikapundung River can be used for fisheries activities on condition that eurytolerant fish are used.